A tiered assessment of human health risks associated with exposure to persistent, mobile and toxic chemicals via drinking water - Whelan, Michael J.; Pemberton, Emma; Hughes, Christopher B.; Swansborough, Chesney; Goslan, Emma H.; Gouin, Todd; Bell, Victoria A.; Bird, Emily; Bull, S.; Segal, L.; Cook, S. H.; Jephcote, Calvin; et al. (Elsevier, 2025)
There is increasing interest in chemicals which are persistent, mobile and toxic (PMT), primarily to protect drinking water. We present a tiered assessment of drinking water exposure and associated human health risks for 22 PMT substances. Worst-case exposure via drinking water is assumed to occur when wastewater is discharged to rivers which are then abstracted for water supply. Screening-level exposures assume daily per capita emissions based on REACH tonnage estimates, with removal in wastewater treatment calculated using SimpleTreat and no riverine dilution. Removal in water treatment was estimated for each substance assuming either conventional or advanced treatment processes. Higher tier spatially-resolved exposures used a gridded routing model which transfers chemical through the landscape based on flow directions derived from a 1 km digital elevation model. Emission was assumed to be proportional to population and no in-stream degradation was assumed. Exposures were calculated for 296 locations containing drinking water treatment works (WTWs) under mean discharge and Q95 (discharge exceeded 95% of the time). At low tiers, risk characterisation ratios (RCRs) were < 1 for all substances, assuming realistic tonnage and conventional treatment. If drinking water is assumed to represent only 20 % of total chemical intake, total RCRs (RCRT) were > 1 for three substances under conventional treatment but were < 1 for all substances under advanced treatment. Highest exposure and RCRs were predicted in highly populated areas with low dilution. RCRT values were > 1 for tetrachloroethylene (highest RCR) at up to 18 % of WTW locations under Q95 conditions assuming conventional treatment. However, RCRT was <1 for all locations assuming advanced treatment. Actual exposures will depend on catchment characteristics, but the model usefully allows prioritising higher risk chemicals and WTWs. Overall, the substances evaluated are unlikely to currently pose health risks, provided an appropriate level of water treatment is employed.
Keywords: 4104 Environmental Management; 40 Engineering; 41 Environmental Sciences; 4004 Chemical Engineering; 4011 Environmental Engineering; Foodborne Illness; 2.2 Factors relating to the physical environment; 3 Good Health and Well Being; 6 Clean Water and Sanitation; Drinking water; Human health; Mobile and Toxic; Organic contaminant; Persistent; Spatial exposure modelling; Tiered risk assessment; Environmental Sciences